2019
DOI: 10.1021/acs.biomac.9b00941
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Bioglass Concentration in 3D Printed Poly(propylene fumarate) Scaffolds for Post-Printing Functionalization with Bioactive Functional Groups

Abstract: Poly(propylene fumarate) (PPF) has shown potential for the treatment of bone defects as it can be 3D printed into scaffolds to suit patient-specific needs with strength comparable to that of bone. However, the lack of specific cell attachment and osteogenic signaling moieties have limited their utility as it is necessary to provide these signals to aid in bone tissue formation. To address this issue and provide a platform for functionalization, Bioglass (∼1−2 μm) microparticles have been incorporated into PPF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Poly(propylene fumarate) (PPF) is a photocrosslinking polymer. Although PPF does not show osteoconductivity or osteoinductivity, it is hypothesized that the addition of bioactive glass promotes its osteogenic properties [85]. In a previous study, 3D-printed PPF-bioactive glass composite scaffolds have been prepared using DLP 3D printing and studied for their bioactivity [85].…”
Section: Thermoset Polymers/bioactive Glass Compositesmentioning
confidence: 99%
“…Poly(propylene fumarate) (PPF) is a photocrosslinking polymer. Although PPF does not show osteoconductivity or osteoinductivity, it is hypothesized that the addition of bioactive glass promotes its osteogenic properties [85]. In a previous study, 3D-printed PPF-bioactive glass composite scaffolds have been prepared using DLP 3D printing and studied for their bioactivity [85].…”
Section: Thermoset Polymers/bioactive Glass Compositesmentioning
confidence: 99%
“…These results indicate that the addition of Bioglass significantly increases thermal degradation of PDLGA during processing, which supports the findings of other J o u r n a l P r e -p r o o f studies 4,5,49 . Other studies investigating the addition of Bioglass into 3D composite scaffolds using 3D printing, did not investigate the effect of Bioglass on the thermal stability of the polymers 2,3 . The effect of Bioglass on the onset temperature was studied further in the Bioglass filaments.…”
Section: Thermal Properties Of Filaments and Scaffoldsmentioning
confidence: 99%
“…Bioglass (based on the system SiO 2 -CaO-Na 2 O and P 3 O 5 ) has been reported to have superior performance in bone regeneration in comparison to other ceramics, however, has had issues in its clinical translation, mainly owning to difficulties with its fabrication into composite/hybrid materials for load bearing applications 1 . Recently several studies, however, have reported more promising results with 3D printing of Bioglass-polymer composites [2][3][4] suggesting that this fabrication technique may be more suitable for Bioglass.…”
Section: Introductionmentioning
confidence: 99%
“…20–29 More importantly, PPF can be conveniently processed into thermosetting elastomers through chemical crosslinking between the unsaturated double bonds in the main chains, which makes it more suitable for biological tissue engineering. Thus, PPF has been mostly used as a raw material for additive manufacturing to design and fabricate engineering scaffolds and thin films with advantageous mechanical and degradation properties, 30–37 promoting the sustainable development of biomaterials and further meeting the clinical demands. Despite the fact that PPF has been extensively studied, it has been barely used as the polymer backbone for synthesizing biocompatible and biodegradable LCP materials.…”
Section: Introductionmentioning
confidence: 99%